Delayed Diagnosis of Scrotal Cancer with Report of Primitive Cells of Difficult Characterization: A Case Report - Gaviria , Luisa María; Villamizar Castellanos, Sebastián; Tirado Romero, Gloria Ibis; Alzate Granados, Juan Pablo; Avendaño Burgos, Daniela (Arandu UTIC, 2025)
This case report presents a delayed diagnosis of scrotal cancer, a rare but aggressive neoplasm with complex histological features due to the presence of primitive cells of difficult characterization. The patient presented with progressive scrotal pain and swelling, leading to the identification of a scrotal mass through imaging studies and histopathological confirmation. Management included complete excision of the mass and lymphadenectomy, followed by adjuvant chemotherapy. Although the patient initially faced a guarded prognosis due to the delay in seeking medical attention, clinical improvement was observed during follow-up. This case highlights the importance of testicular and scrotal self-examination as a key tool for the early detection of abnormalities, as well as the urgency of seeking timely medical care when suspicious symptoms arise.